2022
DOI: 10.1038/s41420-022-01034-0
|View full text |Cite
|
Sign up to set email alerts
|

The pathological role of damaged organelles in renal tubular epithelial cells in the progression of acute kidney injury

Abstract: Acute kidney injury (AKI) is a common clinical condition associated with high morbidity and mortality. The pathogenesis of AKI has not been fully elucidated, with a lack of effective treatment. Renal tubular epithelial cells (TECs) play an important role in AKI, and their damage and repair largely determine the progression and prognosis of AKI. In recent decades, it has been found that the mitochondria, endoplasmic reticulum (ER), lysosomes, and other organelles in TECs are damaged to varying degrees in AKI, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 150 publications
(175 reference statements)
0
14
0
Order By: Relevance
“…Emerging evidence has revealed that the key mechanism of AKI is an uncontrolled burst of toxic reactive oxygen species (ROS) in kidneys, which initiates a chain reaction involving cell apoptosis, necrosis, and excessive inflammation ( Wu et al, 2019 ; Zhao et al, 2021a ; Chen et al, 2023 ). As the second energy-consuming organ of the body, renal tubules with a high density of mitochondria become the main site of ROS production and the target of attack during ischemia or hypoxia ( Tian and Liang, 2021 ; Li et al, 2022 ). ROS storms induce severe oxidative stress, causing irreversible damage to DNA, proteins, and other biomolecules, and ultimately leading to tubular cell dysfunction, i.e., a sudden decline in kidney function ( Weng et al, 2021 ; Zhao et al, 2022a ; Huang et al, 2023a ; Wang et al, 2023a ; Su et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has revealed that the key mechanism of AKI is an uncontrolled burst of toxic reactive oxygen species (ROS) in kidneys, which initiates a chain reaction involving cell apoptosis, necrosis, and excessive inflammation ( Wu et al, 2019 ; Zhao et al, 2021a ; Chen et al, 2023 ). As the second energy-consuming organ of the body, renal tubules with a high density of mitochondria become the main site of ROS production and the target of attack during ischemia or hypoxia ( Tian and Liang, 2021 ; Li et al, 2022 ). ROS storms induce severe oxidative stress, causing irreversible damage to DNA, proteins, and other biomolecules, and ultimately leading to tubular cell dysfunction, i.e., a sudden decline in kidney function ( Weng et al, 2021 ; Zhao et al, 2022a ; Huang et al, 2023a ; Wang et al, 2023a ; Su et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“… 25 , 26 During fission, Drp1 oligomerizes around the mitochondria to form a ring structure that uses the energy generated by GTP hydrolysis to divide the mitochondria. 27 In STZ-induced diabetic mice, the increase in Drp1 expression was accompanied by mitochondrial and cardiac dysfunction. 28 Chen et al indicated that mito-Drp1 is recruited from the cytoplasm to the mitochondria in high glucose-induced podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In various types of AKI, harmful substance accumulation in the tubules leads to disrupted renal redox balance by inducing immune cells, endothelial cells, and RTECs to produce large amounts of RONS [ 74 ]. Furthermore, kidney hypoxia from persistent hypoperfusion, I/R, or microcirculatory disturbances causes intracellular mitochondria to produce large amounts of RONS [ 75 ]. Therefore, RONS overproduction is a central mechanism for the induction of oxidative stress, inflammation, adaptive response, and adaptive responses in AKI.…”
Section: Rons and Akimentioning
confidence: 99%